2010
DOI: 10.4142/jvs.2010.11.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Fatal cases of Theileria annulata infection in calves in Portugal associated with neoplastic-like lymphoid cell proliferation

Abstract: This study was carried out to investigate fifteen cases of acute lethal infection of calves (≤ 4 months of age) by the protozoan parasite Theileria (T.) annulata in the south of Portugal. Calves developed multifocal to coalescent nodular skin lesions, similar to multicentric malignant lymphoma. Infestation with ticks (genus Hyalomma) was intense. Theileria was seen in blood and lymph node smears, and T. annulata infection was confirmed by isolation of schizont-transformed cells and sequencing of hypervariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 37 publications
3
31
0
1
Order By: Relevance
“…T. annulata is mainly transmitted by ticks of the genus Hyalomma; however, similarly to our study, R. bursa was also associated with the transmission of this pathogen in Tunisia (M'Ghirbi et al, 2010). In cattle, T. annulata is the causative agent of tropical theileriosis responsible for serious constraints on the animal health and productivity worldwide due to high morbidity and mortality (Branco et al, 2010;Doliveira et al, 1995). In Portugal, the presence of this tick-borne pathogen has already been reported in cattle during an acute lethal infection of calves highly infested by ticks of the genus Hyalomma (Branco et al, 2010), and during a survey conducted in asymptomatic cattle for detection of piroplasms (Gomes et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…T. annulata is mainly transmitted by ticks of the genus Hyalomma; however, similarly to our study, R. bursa was also associated with the transmission of this pathogen in Tunisia (M'Ghirbi et al, 2010). In cattle, T. annulata is the causative agent of tropical theileriosis responsible for serious constraints on the animal health and productivity worldwide due to high morbidity and mortality (Branco et al, 2010;Doliveira et al, 1995). In Portugal, the presence of this tick-borne pathogen has already been reported in cattle during an acute lethal infection of calves highly infested by ticks of the genus Hyalomma (Branco et al, 2010), and during a survey conducted in asymptomatic cattle for detection of piroplasms (Gomes et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…In cattle, T. annulata is the causative agent of tropical theileriosis responsible for serious constraints on the animal health and productivity worldwide due to high morbidity and mortality (Branco et al, 2010;Doliveira et al, 1995). In Portugal, the presence of this tick-borne pathogen has already been reported in cattle during an acute lethal infection of calves highly infested by ticks of the genus Hyalomma (Branco et al, 2010), and during a survey conducted in asymptomatic cattle for detection of piroplasms (Gomes et al, 2013). Nevertheless, we were not able to identify any study conducted in Portugal that has isolated T. annulata from R. bursa ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic figures were present. Iwama et al [21] and Branco et al [22] observed similar histological features.…”
Section: Discussionsupporting
confidence: 61%
“…In Portugal, the importance of theileriosis is becoming increasingly recognised (Branco et al, 2010;Silva et al, 2010) and a recent epidemiological study determined an increased prevalence in the south of the country. In a crosssectional study in Southern Portugal, around 30% of cattle were found to be infected within an area that represents around 50% of this country's cattle population .…”
Section: Introductionmentioning
confidence: 99%